The vampire diaries. The awakening and the struggle - Smith, L. J. (Lisa J.) (Smith, L. J. (Lisa J.). Vampire diaries, 2007)
Elena: the golden girl, the leader, the one who can have any boy she wants. Stefan: brooding and mysterious, he seems to be the only one who can resist Elena, even as he struggles to protect her from the horrors that haunt his past. Damon: sexy, dangerous, and driven by an urge for revenge against Stefan, the brother who betrayed him. Determined to have Elena, he'd kill to possess her. Collected here in one volume for the first time, volumes one and two of The Vampire Diaries, the tale of two vampire brothers and the beautiful girl torn between them.